(untitled) (Cardiovascular Journal, 2013)
Background: The aim of this study was to evaluate the association between arterial stiffness determined noninvasively by pulse wave analysis (PWA) and the severity of coronary artery disease in patients with acute ST elevation myocardial infarction (STEMI). Methods: This cross sectional study was conducted in the National Institute of Cardiovascular Disease, Dhaka over a period of ten months starting from July 2011 to April 2012. Patients were purposively selected from those who were admitted in NICVD with acute STEMI myocardial infarction agreed to do coronary angiography. Total 99 patients (male: 81, female: 18) were included in this study. Assessment of arterial stiffness was performed noninvasively with the commercially available SphygmoCor system using applanation tonometry with a high-fidelity micromanometer. Augmentation index (AIx), Augmentation pressure (AP) and Augmentation index corrected for heart rate 75beats/min (AIx@75) were derived from this with the technique of PWA. Coronary angiography was performed in those patients during the same hospital stay and severity was assessed by vessel score, Friesinger score and Leaman score. Results: It was found that 9 (9.1%) patients had score 0, 42 (42.4%) had score 1, 23 (23.2%) had score 2 and 25 (25.3%) had score 3. However higher the number of vessels is involved, the greater is the AIx @75. Mean score in single, double and triple vessel disease was 24.50, 33.57 and 34.60 respectively. The mean level of AIx @75 was observed 23.97±11.47 and 31.76±11.26 in insignificant and significant CAD respectively using Friesinger score. The difference was statistically significant (p<0.05). Spearman correlation analysis demonstrated a positive correlation between the AIx@75 and the severity of coronary artery disease (p= <0.05, r=0.40). Conclusion: In conclusion, the results presented herein indicate that augmentation pressure (AP), augmentation index (AIx), and augmentation index corrected for heart rate 75/minute (AIx@75), measures closely related to wave reflections and arterial stiffness, are predictors of severity of CAD. It may be considered as a recommended test for the evaluation of CV risk in addition to other routine investigations DOI: http://dx.doi.org/10.3329/cardio.v5i2.14281 Cardiovasc. j. 2013; 5(2): 133-140